2022
DOI: 10.2217/rme-2022-0095
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Exosomes Induce Cell Proliferation and Wound Healing in Human Endometrial Cells

Abstract: Aim: To investigate the regenerative effects of a platelet-derived purified exosome product (PEP) on human endometrial cells. Materials & methods: Endometrial adenocarcinoma cells (HEC-1A), endometrial stromal cells (T HESC) and menstrual blood-derived stem cells (MenSC) were assessed for exosome absorption and subsequent changes in cell proliferation and wound healing properties over 48 h. Results: Cell proliferation increased in PEP treated T HESC (p < 0.0001) and MenSC (p < 0.001) after 6 h and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Based on nanoparticle tracking analysis (NTA), the EVs isolated from human blood platelets (PEV) used in this study averaged 208.2 ± 13.3 nm in diameter with two modal peaks at 150–200 and 210–240 nm ( Figure a). The concentration of PEV after reconstitution from lyophilized product at 1 mg mL −1 phosphate‐buffered saline (PBS) was 9.4 × 10 9 particles mL −1 , as previously, [ 57 ] and 250 µL injections at this concentration were given over three consecutive days either during the innate immune response ( Figure a) or during myocarditis (Figure 2b). Transmission electron microscopy (TEM) confirmed several essential EV characteristics including the presence of a defining membrane, spherical shapes, and distinct contents within the vesicles (Figure 1b; Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Based on nanoparticle tracking analysis (NTA), the EVs isolated from human blood platelets (PEV) used in this study averaged 208.2 ± 13.3 nm in diameter with two modal peaks at 150–200 and 210–240 nm ( Figure a). The concentration of PEV after reconstitution from lyophilized product at 1 mg mL −1 phosphate‐buffered saline (PBS) was 9.4 × 10 9 particles mL −1 , as previously, [ 57 ] and 250 µL injections at this concentration were given over three consecutive days either during the innate immune response ( Figure a) or during myocarditis (Figure 2b). Transmission electron microscopy (TEM) confirmed several essential EV characteristics including the presence of a defining membrane, spherical shapes, and distinct contents within the vesicles (Figure 1b; Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The ECM, cytoskeleton, transmembrane proteins, and multiple signaling pathways are involved in this signaling. It is worth noting that extracellular vesicles are also important in this context, with their role in cell adhesion, cell-to-cell adhesion, migration, and proliferation [9][10][11]19,20,[23][24][25]29]. The demonstrated elevated expression of genes mainly related to the processes of migration, proliferation, and granulosa cell adhesion clearly suggests that exosomes are important in these processes.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, exosomes transporting protein molecules released from cells have been suggested to promote cell migration, as described in inflammatory processes [19]. Recent reports have also indicated that exosomes are actively involved in the processes of proliferation [20] and the response to hypoxia [21]. Exosomes affect the composition of the ECM (through its remodeling), but, at the same time, the ECM affects the release of exosomes from the cell [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report suggests cell proliferation and wound healing in in vitro human endometrial cell lines when exposed to platelet-derived exsosomes. 98 Exploration of uterus transplantation 99 and early bioengineering of the uterus is underway, 100 but the clinical role of these for Asherman syndrome remains unknown. A focus on early detection and treatment at experienced health care centers remains critical for individuals desiring future fertility.…”
Section: Postoperative and Obstetric Outcomesmentioning
confidence: 99%